2009
DOI: 10.1164/rccm.200901-0135oc
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Tobacco Smoke Exposure Affects Global and Gene-specific DNA Methylation

Abstract: Rationale: Prenatal exposure to tobacco smoke increases the risk for diseases later in the child's life that may be mediated through alterations in DNA methylation. Objectives: To demonstrate that differences in DNA methylation patterns occur in children exposed to tobacco smoke and that variation in detoxification genes may alter these associations. Methods: Methylation of DNA repetitive elements, LINE1 and AluYb8, was measured using bisulfite conversion and pyrosequencing in buccal cells of 348 children part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
425
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(447 citation statements)
references
References 33 publications
15
425
1
6
Order By: Relevance
“…However, we used the most technologically advanced and validated methods currently available for LINE-1 methylation analysis and have already demonstrated a relationship between higher LINE-1 and male sex and several other obesity-related risk factors in offspring in early life. 17 This method for LINE-1 methylation analysis has been shown in previous investigations to be sensitive to environmental and host-related factors, including age, 18 sex, 16,19 smoking 20 and tobacco smoke components, 21 physical activity 22 and environmental pollution. [23][24][25][26] Also, we measured DNA methylation only in blood DNA and we cannot exclude that methylation changes due to dietary components might be present in other tissues in the same individuals.…”
Section: Resultsmentioning
confidence: 99%
“…However, we used the most technologically advanced and validated methods currently available for LINE-1 methylation analysis and have already demonstrated a relationship between higher LINE-1 and male sex and several other obesity-related risk factors in offspring in early life. 17 This method for LINE-1 methylation analysis has been shown in previous investigations to be sensitive to environmental and host-related factors, including age, 18 sex, 16,19 smoking 20 and tobacco smoke components, 21 physical activity 22 and environmental pollution. [23][24][25][26] Also, we measured DNA methylation only in blood DNA and we cannot exclude that methylation changes due to dietary components might be present in other tissues in the same individuals.…”
Section: Resultsmentioning
confidence: 99%
“…This does not rule out the possibility that a minority of genes are influenced by a common environment. Indeed, previous genome-scale studies of DNA methylation have found a range of probes significantly associated with maternal environmental, from 0.6% (Breton et al 2009) and 1.1% (Fryer et al 2011) to 23% (Katari et al 2009). Because the accuracy of the estimation of effect size depends on study power, further investigation in larger numbers of twins is needed (Visscher 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we did not assess second hand smoke exposure in our patient population. Environmental exposures such as smoking or second hand smoking are known epigenetic modifiers via DNA methylation [34][35]. Epigenetic changes can additionally be affected by diet and aging [36][37].…”
Section: Discussionmentioning
confidence: 99%